Inflammatory mediators of proliferative vitreoretinopathy: hypothesis and review - Dai, Ying; Dai, Chenghua; Sun, Tao (International ophthalmology, 2020)
Purpose To review the role of inflammatory mediators in proliferative vitreoretinopathy (PVR) development and the current treatment for PVR prevention. Methods A PubMed search was carried out using these keywords “PVR,” “inflammatory mediators,” “growth factors,” “cytokines” and “treatment.” Studies regarding inflammatory mediators and PVR therapy were included and published up to December 2019. Results Inflammatory mediators, namely growth factors and cytokines, have been implicated in the occurrence and development of PVR. Among various inflammatory mediators, transforming growth factor-β, platelet-derived growth factor, interleukin-6, interleukin-8 and tumor necrosis factor-α are considered to be particularly important. In this review, we focus on the hypothesis that growth factors and cytokines are involved in the development of PVR, and current treatment for the prevention of PVR. Conclusion We support the hypothesis that growth factors and cytokines may participate in the complex process of PVR development. More importantly, the identification of inflammatory mediators provides novel and efficacious therapeutic targets for the treatment of PVR.